Mkhaʼ ʼgroʼi bsun zlog bźugs so - Rgod-tshaṅ-pa Mgon-po-rdo-rje, 1189-1258 (Rgod-tshaṅ sgrub sde, 1971)
Drukpa Kargyudpa devotional text; traditionally regarded to have been composed by the heavenly dakini ʼGro-ba-bzaṅ-mo for the benefit of Rgod-tshaṅ-pa Mgon-po-rdo-rje.